Mechanochemical Synthesis and Physicochemical Characterization of Isoniazid and Pyrazinamide Co-crystals With Glutaric Acid - Ngilirabanga, Jean Baptiste; Aucamp, Marique; Pires Rosa, Paulo; Samsodien, Halima (Frontiers in Chemistry, 2020)
The present work reports two novel pharmaceutical co-crystals INHGA and PGA in a 2:1 ratio synthesized using two first-line anti-tubercular drugs isoniazid and pyrazinamide with pentanedioic (glutaric) acid as co-crystal former. The co-crystals were produced via solid-state and solvent assisted grinding methods. Thermal characteristics of the samples were obtained using the differential scanning calorimetry, hot stage microscopy, and thermogravimetric analyses. The morphology of the powder samples by scanning electron microscopy, structural analysis by Fourier transform infrared spectroscopy and powder X-rays diffraction ensured co-crystal formation. Thermal analyses confirmed the co-crystals with new melting transitions ranging between their respective starting materials. Unique morphologies of the co-crystal particles were clear in SEM micrographs. The formation of intermolecular interactions with the co-crystal former was confirmed by the FTIR spectral band shifting and was supported by distinct PXRD patterns of co-crystals thereby authenticating the successful co-crystal formation. In vitro solubility evaluation of the synthesized co-crystals by HPLC suggested a remarkable increase in solubility of both INH and PZA in their respective co-crystals.